Factor analysis of ancient population genomic samples - Olivier François (Nature Portfolio, 2020)
Principal component analysis is often used in studies of ancient DNA, but does not account for the age of the samples. Here, the authors present a factor analysis (FA) which corrects for this by including the effect of allele frequency drift over time.